2019
DOI: 10.1111/bld.12280
|View full text |Cite
|
Sign up to set email alerts
|

Staff experiences working in community‐based services for people with learning disabilities who show behaviour described as challenging: The role of management support

Abstract: Accessible summary We looked at staff working with people with a learning disability and challenging behaviour. We tried to find out if managers' help their staff to work better. We looked at how often staff saw their manager and if their manager tried to help their staff to work better or spent more time doing office work. We found out that when managers helped staff to work better, staff feel better about their work. Even when staff did not see their manager very often, other staff were helping them to do … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 30 publications
(71 reference statements)
0
18
0
Order By: Relevance
“…Also, on the exosystem level, staff turnover of direct staff members and need for extra financial means is associated with challenging behaviours. In addition to sufficient staff and financial resources, Bigby and Beadle-Brown (2018) emphasised the importance of proper front-line management and human resources policies and practices in order to provide guidance to staff to be able to enhance residents' quality of life, which in turn may influence their challenging behaviour ( Josefsson et al., 2018 ; Deveau and McGill, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, on the exosystem level, staff turnover of direct staff members and need for extra financial means is associated with challenging behaviours. In addition to sufficient staff and financial resources, Bigby and Beadle-Brown (2018) emphasised the importance of proper front-line management and human resources policies and practices in order to provide guidance to staff to be able to enhance residents' quality of life, which in turn may influence their challenging behaviour ( Josefsson et al., 2018 ; Deveau and McGill, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, staff members who feel that they are permitted to make mistakes in providing support to residents are better able to learn from these mistakes and adjust their actions in subsequent incidents involving challenging behaviour ( Knotter et al., 2013 ; Olivier-Pijpers et al., 2019 ). Exosystem aspects that seem to be associated with challenging behaviour include the management's leadership style, coaching by psychologists, a supportive team environment for care professionals, a positive organisational culture and the translation of personnel policies into daily practices; all of these aspects provide the staff guidance on proper support of residents, resulting in the occurrence of fewer incidents involving challenging behaviour ( Dilworth et al., 2011 ; Allen et al., 2013 ; Deveau and McGill, 2016 , 2019 ; Bigby and Beadle-Brown, 2018 ; McGill et al., 2018 ; Olivier-Pijpers et al., 2018 ; Olivier-Pijpers et al., 2019 ). Macrosystem aspects linked to challenging behaviour include negative media attention to bad practices, which results in a focus on control instead of trust of staff members to support residents, in turn negatively influencing challenging behaviour ( Olivier-Pijpers et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, a particular style of management focused upon developing staff practice called ‘practice leadership’ (and good general management) are important factors for implementing 'active support' (Beadle‐Brown et al, ). Frontline managers also have an important role in ameliorating potential negative experiences for staff when they have to support service users who may show behaviour described as challenging (Deveau & McGill, , ).…”
Section: Introductionmentioning
confidence: 99%
“…This study has value for researchers and practitioners, as the ecological perspective provides insight into recent studies on implementing and maintaining active support in various services, which have concluded that hands-on training and managerial leadership seem to be crucial organizational aspects (Beadle-Brown, Bigby, & Bould, 2015;Bigby & Beadle-Brown, 2018;Bigby, Bould, Iacono, Kavanagh, & Beadle-Brown, 2019;Deveau & McGill, 2016a, 2016b. As Bould, Beadle-Brown, Bigby, and Iacono (2016) (Deveau and McGill, 2019;Deveau, Gore, & McGill, 2020;Olivier-Pijpers, et al, 2018;Schippers, 2019;Tournier et al, 2020;Walker, 2012). During organizational changes, continuous discussions on aligning staff attitudes with the organizational vision, staff training in positive attitudes and reduced restraint use, and sufficient information about residents' needs to enhance resident-staff bonding are also necessary (Olivier-Pijpers, Cramm, & Nieboer, 2019;Philips & Rose, 2010;Walker, 2012).…”
Section: Discussionmentioning
confidence: 96%
“…budget cuts, self-organising staff teams) led to changes within staff teams and how they functioned, as indicated in the focus groups and meeting records. (Deveau & McGill, 2019;Deveau, Gore, & McGill, 2020;Olivier-Pijpers, et al, 2018;Olivier-Pijpers et al, 2019;Tournier, Hendriks, Jahoda, Hastings, & Embregts, 2020). changes (Deveau & Leitch, 2020;Ravoux, et al, 2012;Tournier et al, 2020).…”
Section: Staff's Feelings Of Being Unheardmentioning
confidence: 99%